A Case of Severe Hydroxychloroquine-Induced Retinal Toxicity in a Patient with Recent Onset of Renal Impairment: A Review of the Literature on the Use of Hydroxychloroquine in Renal Impairment. (9th December 2012) - Tailor, Rajen; Elaraoud, Ibrahim; Good, Peter; Hope-Ross, Monique; Scott, Robert A. H.
Abstract : We present a case of a 67-year-old female who presented with a twelve-month history of progressive blurred vision in both eyes. The patient was on hydroxychloroquine 200 mg twice a day for eight years for the treatment of scarring alopecia. Two years prior to presenting, the patient was found to have chronic kidney disease stage 3 secondary to hypertension. Examination revealed bilateral reduced visual acuities with attenuated arterioles and pigmentary changes on retinal assessment. Goldmann visual fields showed grossly constricted fields in both eyes. The patient was diagnosed with retinal toxicity secondary to hydroxychloroquine probably potentiated by renal impairment. Risk factors for retinal toxicity secondary to hydroxychloroquine can be broadly divided into dose-related and patient-related factors. Our patient developed severe retinal toxicity despite being on the recommended daily dose (400 mg per day). Although retinal toxicity at this dose has been documented, the development of renal impairment without dose adjustment or close monitoring of visual function is likely to have potentiated retinal toxicity. This case highlights the need to monitor renal function in patients on hydroxychloroquine. Should renal impairment develop, either the drug should be stopped or the dose reduced with close monitoring of visual function by an ophthalmologist.